Da’wa Method Ning Umi Laila in Youtube Video “Ibu ibu Luweh Seneng Pengajian Opo Rasan-Rasan” - Pipin Seltika (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
The more advanced the age then, the way of delivering the message also becomes more modern and follow the trend that evolves amongst the society. The same is true of the preachers who have different methods so that their message can be accepted by their mad’s. In this rapid development of technology many electronic media can be used as a means of distribution of fame like Youtobe, Tik tok, Instagram, Facebook and so on. This research was used to find out the method of praise of Ning Umi Laila in her YouTube video entitled "Mothers Luweh Pleased Studying Opo Rasan-rasan". In this process, the author uses qualitative research using methods of content analysis. Primary and secondary data collection techniques. The result of the study this time shows that Ning Umi Laila is one of the women who are still said to be fairly young, but even so his teachings can be accepted in all categories because the teachings method used is the teaching methods bill of things that is the compatibility of behavior to be followed, Mauidzah Hasanah that is gentleness in speaking words, Bil Hikmah that is teaching the way of God by using wisdom, and the last one is his teaching while using Islamic songs and Sholawat as the method of teaching, it is done so that his teaches do not get bored and revive the spirit of the listeners (mad’u).